HUBUNGAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA NELAYAN DI KELURAHAN LAKOLOGOU KECAMATAN KOKALUKUNA KOTA BAUBAU - Muhirin Muhirin; Usman Rianse; Megafirmawanti Lasinta (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The considerable potential inherent in Indonesia's fisheries sector, bolstered by its abundant marine resources, has not been met by a commensurate enhancement in the productivity of fishermen. This underperformance can be primarily attributed to the limited competencies exhibited by fishermen, characterized by a paucity of knowledge, skills, and attitudes. A case in point is the traditional fishermen in Lakologou Village, Baubau City, who continue to grapple with challenges related to nature, technology, and catch management. The objective of this study is to ascertain the correlation between competence and work productivity among fishermen in Lakologou Village. The research population consisted of fishermen who use motorboats in Lakologou Village, with a total of 26 respondents. The research sample was determined using the census method.  The data were collected through a combination of interviews, documentation, and surveys administered via a questionnaire. The research variables were subsequently divided into two categories: fisherman competency and fisherman productivity. Quantitative statistical analysis was utilized in this study. The results indicated that the competence of fishermen in Lakologou Village was in the good category, reflecting their ability to adequately master knowledge, skills, and work attitudes in fishing activities. The productivity of fishermen was also notably high, as evidenced by their capacity to achieve optimal catches, maintain the quality of marine products, and demonstrate work efficiency in the field. A correlation analysis reveals a robust and statistically significant relationship between the competence of fishermen and their work productivity. This indicates that an enhancement in competence leads to a direct increase in productivity. This finding underscores the significance of enhancing the capabilities of coastal human resources through training programs and the transfer of technological expertise. These measures are instrumental in enhancing the competitiveness and sustainability of the fisheries sector.